ANALISIS HASIL UJIAN NASIONAL BAHASA INGGRIS SMA DAN PENGEMBANGAN MODEL PENINGKATAN MUTU PEMBELAJARAN BAHASA INGGRIS DI PROPINSI NUSA TENGGARA BARAT - I Made Sujana; Yayuk Andayani; Baidowi Baidowi; M. Liwa Ilhamdi; Ni Made Novi Suryanti; Mari’i Mari’i (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2016)
Abstract. This research aims at (a) mapping of the results of National Examinantion of Senior High Schools in Mataram City, West Lombok Regency and North Lombok Regency, (b) finding out the sources of possible problems, (c) providing recommendation for solutions, and (d) designing solution models. Data are collected in two levels: for English National Examination mapping, all 52 schools are analyzed; while for finding out the sources of problems and recommendation, only 12 schools involved as samples, the selection of which employ purposive quota sampling technique, by considering types of schools (government and private), location (city or country), achievement/rank in national Exam (high or low). The data are collected using triangulation techniques such as documentary, questionnaire for schools and for teachers, observation, probing test, and focus group discussion (FGD). The collected data are then analyzed qualitatively and quantitatively. From the analysis, it is concluded that (i) the mastery of English subject tends to increase from 2008 to 2009 and 2010; (ii) There are at least 10 indicators on Listening and 14 indicators on Reading whose achievement is under 60% and regarded as problematic indicators to the students for 3 years; (iii) Factors causing those problems are KTSP and 8 National Standards of Education in most schools have not been implemented and fulfilled optimally, caused by various factors; (iv) From the analysis of factors influencing the improvement of quality at SMAs, one of the major problems is teachers capability in relation to other Standards (Content, Process, Assessment, Facilities and Teachers Development). Solving teachers’ problems are expected to solve other problems; (v) It is, therefore, that in order to improve the quality of education in Senior High Schools in the targeted regions, the solution model offered is the empowerment of English teachers at the targeted regions.Keywords: National Exam, Senior High School, solution recommendation